U.S. County-Level Natality and Mortality Data, 1915-2007 - Bailey, Martha ([Verlag nicht ermittelbar], 2016)
This collection contains information on county-level vital events that occurred in the United States from 1915-2007. When sources allow, data are disaggregated by county of occurrence, county of residence, and race. The data include information on vital events such as the number of infant deaths, births to unmarried women, births in the presence of hospital attendants, and infant birth weight.